Duolingo Applications as Vocabulary Learning Tools - Sarlita D Matra (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Online applications recently are seen to be effective and attractive tool in mastering vocabulary. Teachers have done many efforts and innovation in classroom management and relevant teaching media in order to improve teaching and learning qualities. The use of computer assisted language learning (CALL) nowadays become a topic that still relevant to be discussed in the world of education as one of the solution to deal with 4.0 industrial revolution. The objectives of research were:1) To describe the implementation of Duolingo application in teaching vocabulary. 2) To describe the effectiveness of Duolingo application in teaching vocabulary. The researcher used Cluster Random Sampling. The instruments used by the writer were test, interview, questionnaire and documentation. The technique of data analysis employed was paired sample t-test. The result of thestudy: 1) Duolingo application can be implemented to the seventh grade students of Mts. Gondang Wonopringgo Pekalongan. The steps were as follows; first, the student must open their browser tab and typed www.duolingo.com. After redirection, the students chose the language they wanted to learn (in this research they chose English). Next, the students filled the account using their name and email address. Facebook and google account can be used as well to sign up if they already have one. After doing sign up/login process, the students had to complete the task given by Duolingo starts from basic 1 until test phase. Student’s comprehension can be evaluated through the test which can be accessed through https://englishtest.duolingo.com. 2). The students’ score after taught by using Duolingo application showed significant result. The result showed that P-value < 0,05, it means that there were any significant influences between score of pre-test and post-test. It can be concluded that Duolingo application is effective in teaching vocabulary at the seventh grade students of Mts. Gondang Wonopringgo Pekalongan in the academic year of 2018/2019. Therefore, the writer suggested that Duolingo application can be one of alternative media to teach English for young learners. Keywords: Application, Duolingo, English, Teaching Media, Vocabulary